Review: Characterisation and Dissolution of Low Solubility Active Substances in S-SNEDDS Preparations with Various Manufacturing Methods - Rodhia Ulfa; Husnun Khairunnisa’ Pratiwi (Universitas Sebelas Maret, 2025)
SNEDDS is composed of a drug, surfactants, co-surfactants, and oils. Developing and optimising the correct formulation is necessary to minimise time and expense, and ensure the correct formulation. This review aimed to determine the characteristics and solubility of S-SNEDDS preparations made employing various manufacturing methods and the most effective and efficient drying procedures for low-water-soluble active ingredients. The method utilised was a literature study technique, which involved searching for literature in the form of primary data in the form of national and international journals published in the last ten years, starting from 2011 to 2021. The methods of making S-SNEDDS examined were adsorption to the solid carrier, spray drying, and freeze-drying using various dryers. The method of producing S-SNEDDS, adsorption to a solid carrier, possessed better characteristics and dissolution of the drug than the other two methods. The recommended drier was Aerosil 200, which effectively binds moisture and produces powder characteristics that fulfill the requirements.